Pollarding and root pruning as management options for tree-crop competition and firewood production - Sande, Bueno Dickens (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScFor) (Forest and Wood Science)--University of Stellenbosch, 2003.